Sosialisasi Pemanfaatan Tanaman sebagai Obat dan Kosmetika - Muhsin, Lalu Busyairi; Baiq Yulia Hasni Pratiwi; Sri Winarni Sofya; Muhammad Eka Putra Ramandha; Eka Nurul Qomaliyah; Nyoman Bagus Aji K (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The utilization of plants as medicine and cosmetics is essentially plants with medicinal properties that are grown on yard land managed by families. These plants are planted in order to fulfill the family's need for traditional medicines that can be made and grown at home. The benefits are to fulfill the need to overcome health problems traditionally (medicine). The crops are planted in order to fulfill the family's need for traditional medicines that can be made and grown at home. The benefits are to fulfill the need to overcome health problems traditionally (medicine). Therefore, it is very important to carry out a planting movement in the surrounding environment not only at home, for example in the school.  In this community service research, one of them aims to carry out a planting and utilization movement in the women's dormitory environment. This can also increase the interaction of students with nature and its utilization can provide a preventive benefit in overcoming health problems in the school environment.  The results of the assistance of community service activities regarding the partnership program on planting and utilization assistance. Medicinal and cosmetic plants at MAN 3 Mataram, showed significant results in several things such as students being able to plant and utilize medicinal and cosmetic plants in the environment.